Hospitalization for drug‐induced hepatotoxicity: linking Y‐codes with pharmaceutical claims data to identify implicated medicines. (14th February 2015) - Nguyen, T. A.; Caughey, G.; Pratt, N.; Shakib, S.; Kemp, A.; Roughead, E.
Summary What is known and objective Hospital admissions associated with an adverse drug reaction are often coded to the International Classification of Diseases external cause Y‐codes, denoting the medicine class deemed to cause the adverse drug reaction. Matching hospital data with outpatient dispensing data has the potential to identify the specific causative medicines but the ability to identify the causative medicines in this way has not been previously assessed. This study aimed to determine the proportion of Y‐coded hospitalizations for drug‐induced hepatotoxicity that could be matched with a potential causative medicine from outpatient dispensing data. Methods A retrospective cohort study was undertaken from 1 Jan 2005 to 30 June 2012 using data from the Australian Government Department of Veterans' Affairs of all admissions coded to drug‐induced hepatotoxicity. Medicine use in the 6 months prior to hospitalization was examined to identify the probable causative medicines. Results and discussion Thirty five admissions were identified for 31 patients. All admissions were preceded by use of medicines known to cause hepatotoxicity. Twenty four admissions had a Y‐code recorded, of which 19 admissions had at least one Y‐code specifying the causative medicine class (22 Y‐codes). Of the 22 Y‐codes, 95% could be successfully matched with a medicine from the same class that had been dispensed in the 6 months prior to admission. Further, 92% were preceded by use of multiple hepatotoxic medicines. What is new and conclusion Results of our study demonstrate that hospital administrative data can be linked to prescription dispensing data to identify specific medicines suspected of causing the adverse drug reaction.